Management of Post-Traumatic Dental Care Anxiety in Pediatric Dental Practice-A Clinical Study - Twana Othman Hussein; Damla Akşit-Bıçak (MDPI AG, 2022)
Background: It is important to avoid giving children traumatic dental experiences that induce post-traumatic dental care anxiety (PTDA) in clinical dental practices. The aim of this study was to evaluate whether non-pharmacological behavior management procedures can effectively reduce the use of pharmacological behavior management in children who have PTDA and are referred for regular dental treatments under general anesthesia (GA) and sedation. Methods: This clinical study consisted of two groups. The treatment group involved 20 healthy children aged 4-14 with PTDA and also those referred by other institutions for dental treatment with/without GA. The control group was sampled retrospectively from the patient records and involved 20 healthy uncooperative children aged 4-14 with PTDA who had been treated under GA. Results: The number of multiple appointments was significantly higher in the treatment group than in the control group. Only 25% of children in the treatment group underwent GA and the rest (75%) were managed with non-pharmacological management techniques. Nine (60%) children who were treated with minimally invasive techniques did not require GA. Conclusions: It is important to treat children as much as possible without causing PTDA by using appropriate behavior management techniques. This study emphasizes the usefulness of thoroughly employing non-pharmacological behavior management methods before directing a child with PTDA for dental treatment under pharmacological behavior management, which can prevent the over-utilization of sedation and GA.